Cybersecurity and Geopolitics in the Dominican Republic: Threats, Policies and Future Prospects - Tapia, Johan (2023)
Cybersecurity, an increasingly pertinent topic in today's globalized world, is the central focus of this paper, which provides a comprehensive guide to the cybersecurity landscape in the Dominican Republic. The authors delve into the country's cyber threats and vulnerabilities, its current cybersecurity policy, the interplay between cybersecurity and national security, and the role of diplomacy in addressing cybersecurity issues. The paper also presents real-world examples of cyberattacks and cybersecurity responses in the Dominican Republic, and discusses future prospects for cybersecurity in the country. Cyberattacks pose a constant threat to national security, economies, and critical infrastructure worldwide. As these issues transcend national borders, international collaboration becomes critical in confronting these threats and safeguarding global citizens and institutions. This paper aims to not only shed light on the specific case of the Dominican Republic but also serve as a reference for other contexts. The methodology, results, and conclusions drawn from the analyzed texts will be detailed in the subsequent sections of the paper.